2015
DOI: 10.1093/cid/civ837
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Molecular Diagnostics, Antibiotic Treatment Decisions, and Developing Approaches to Inform Empiric Therapy: PRIMERS I and II

Abstract: Background. Rapid molecular diagnostic (RMD) platforms may lead to better antibiotic use. Our objective was to develop analytical strategies to enhance the interpretation of RMDs for clinicians.Methods. We compared the performance characteristics of 4 RMD platforms for detecting resistance against β-lactams in 72 highly resistant isolates of Escherichia coli and Klebsiella pneumoniae (PRIMERS I). Subsequently, 2 platforms were used in a blinded study in which a heterogeneous collection of 196 isolates of E. co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 19 publications
(20 reference statements)
1
33
0
Order By: Relevance
“…With the assumption of 5% carbapenem resistance in a given population, the tests both predicted susceptibility correctly in >95 % of cases, whereas prediction of resistance was only 41-50%, dependent on test method. 16 A further complication of nucleic-acid based molecular testing is the occasional occurrence of isolates that test positive for a carbapenemase gene, but are susceptible in vitro to the carbapenems. For instance, isolates that test susceptible to ertapenem, meropenem and imipenem, but harbor the bla KPC gene, have been described.…”
Section: Rapid Nucleic Acid-based Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the assumption of 5% carbapenem resistance in a given population, the tests both predicted susceptibility correctly in >95 % of cases, whereas prediction of resistance was only 41-50%, dependent on test method. 16 A further complication of nucleic-acid based molecular testing is the occasional occurrence of isolates that test positive for a carbapenemase gene, but are susceptible in vitro to the carbapenems. For instance, isolates that test susceptible to ertapenem, meropenem and imipenem, but harbor the bla KPC gene, have been described.…”
Section: Rapid Nucleic Acid-based Testsmentioning
confidence: 99%
“…13,18 More research is needed to understand the clinical significance of such discordance and how best to treat isolates that contains a "silent" carbapenemase gene, yet displays carbapenem susceptibility. 16 Tests performed directly from blood cultures and clinical specimens Two tests are currently available that detect carbapenemase genes in bacteria present in blood: the FilmArray Ò Blood Culture Identification Panel (BCID, BioFire Diagnostics LLC, Salt Lake City, UT) and the Verigene Ò Gram-negative blood culture test (Nanosphere, Northbrook, IL). Both tests require blood to be cultured on a standard laboratory automated blood culture system prior to testing.…”
Section: Rapid Nucleic Acid-based Testsmentioning
confidence: 99%
“…for the presence or absence of the genetic targets (carbapenemase genes) that are known to be associated with CR, as previously described (13,14). In brief, PCR/ESI-MS is a nucleic acid amplification technology that targets select genes using "smart primers," determines their exact mass, and then uses algorithms to define the target gene identified (1). The PCR/ESI-MS platform also provides genus-and species-level identification.…”
Section: Methodsmentioning
confidence: 99%
“…In the platforms for rapid identification of multidrug-resistant gram-negative bacteria and evaluation of resistance studies (PRIMERS) I and II, analytical strategies were developed and tested to evaluate whether genotypic results obtained by nucleic acid amplification technologies could identify susceptibility and resistance to beta-lactam antibiotics using a carefully chosen panel of susceptible and highly beta-lactam-resistant Enterobacteriaceae (1). The rapid molecular diagnostic (RMD) platforms that formed the testing basis for that investigation were (i) PCR coupled with electrospray ionization mass spectrometry (PCR/ESI-MS); (ii) molecular beacons (MB); (iii) a DNA microarray kit; and (iv) a next-generation sequencing platform.…”
mentioning
confidence: 99%
“…Many questions remain about the relative utility and most appropriate combination of phenotypic and genotypic assays for antibiotic resistance and integration with healthcare "big data" systems. 43,44 Case reports and case series have shown that FMT can effectively reduce the overall number of antibiotic resistance genes as well as eradicate colonic colonization by MDRO. 45,46 Some have advocated for a whole genome sequencing approach to screening for antibiotic resistance while others have indicated that the field is changing too rapidly to establish actionable/understandable platforms and that this approach is much more costly.…”
Section: Antibiotic Resistance Screening and The Resistomementioning
confidence: 99%